Sosialisasi IBIFest 4.0 Literasi Digital: Berpikir Kritis di Era Kekinian - Kristantini, Aryanti; Permana, Dwi; Kurniawan, Ari; Fatwara, Medy Desma (Yayasan Sagita Akademia Maju, 2023)
This abdimas activity aims to raise important issues related to digital literacy and critical thinking in the context of an increasingly connected digital era. This activity responds to the rapid development of technology and information, where digital literacy is the key to accessing, understanding, and participating in an increasingly complex digital world. At the same time, critical thinking skills are becoming increasingly important to deal with challenges such as the spread of misinformation and the wise use of technology. This activity increased participants' understanding of digital literacy and critical thinking and recognition of the importance of these skills in facing digital challenges. It develops participants' critical thinking skills through interaction, discussion and reflection on related topics.